Does Strict Employment Protection Legislation Influence The Rate Of Workplace Accidents?. (15th July 2019) - Radulescu, Roxana; Robson, Martin
Abstract : This paper explores the correlation between employment protection legislation (EPL) and the rate of workplace accidents, using a theoretical model and data for OECD countries. EPL has been rolled back in most OECD countries since the mid‐80s. In parallel, there has been a decrease in the number of workplace accidents reported, especially non‐fatal ones. We ask the question whether less employment protection could have contributed to the reduction in accident rates, e.g. by reducing workers' willingness to report accidents. To investigate, we build a theoretical model, which suggests that the incentives to report workplace accidents are complex and could even result in a negative relationship between EPL and accident reporting. It is possible, e.g. that labour market reforms reduce job security and incentivise behaviours that bring immediate benefits, like accident reporting. The empirical analysis, using a database of 16 OECD countries, supports the view that the dilution of EPL for regular contracts has increased the rate of accident reporting. This result is robust after controlling for a number of other factors, such as the unemployment rate, economic growth, unemployment benefits, trade union density and temporary work.